ON SOME NEW OPERATIONS OF FUZZY SOFT SETS - NEOG*, TRIDIV JYOTI; DUTTA, BIJU KUMAR (International Journal of Mathematical Archive, 2018)
The purpose of this paper is to study the notion of disjunctive sum, difference and symmetric difference of fuzzy soft sets and their basic properties. Finally we have put forward a decision making problem using the notion of cardinality of fuzzy soft sets.